Interconnections: bridges, routers, switches, and internetworking protocols - Perlman, Radia 1951- (Boston, Addison-Wesley:, 2000)
[Radia Perlman's Interconnections is recognized as a leading text on networking theory and practice. It provides authoritative and comprehensive information on general networking concepts, routing algorithms and protocols, addressing, and the mechanics of bridges, routers, switches, and hubs. This Second Edition is expanded and updated to cover the newest developments in the field, including advances in switching and bridge technology, VLANs, Fast Ethernet, DHCP, ATM, and IPv6. Additional new topics include IPX, AppleTalk, and DECnet. You will gain a deeper understanding of the range of solutions possible and find valuable information on protocols for which documentation is not readily available elsewhere. Written by the inventor of many of the algorithms that make switching and routing robust and efficient, Interconnections, Second Edition offers an expert's insight into how and why networks operate as they do. Perlman describes all of the major networking algorithms and protocols in use today in clear and concise terms, while exploring the engineering trade-offs that the different approaches represent.] [Radia Perlman's Interconnections is recognized as a leading text on networking theory and practice. It provides authoritative and comprehensive information on general networking concepts, routing algorithms and protocols, addressing, and the mechanics of bridges, routers, switches, and hubs. This Second Edition is expanded and updated to cover the newest developments in the field, including advances in switching and bridge technology, VLANs, Fast Ethernet, DHCP, ATM, and IPv6. Additional new topics include IPX, AppleTalk, and DECnet. You will gain a deeper understanding of the range of solutions possible and find valuable information on protocols for which documentation is not readily available elsewhere. Written by the inventor of many of the algorithms that make switching and routing robust and efficient, Interconnections, Second Edition offers an expert's insight into how and why networks operate as they do. Perlman describes all of the major networking algorithms and protocols in use today in clear and concise terms, while exploring the engineering trade-offs that the different approaches represent.]